2014
DOI: 10.1063/1.4861168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular doping for control of gate bias stress in organic thin film transistors

Abstract: The key active devices of future organic electronic circuits are organic thin film transistors (OTFTs). Reliability of OTFTs remains one of the most challenging obstacles to be overcome for broad commercial applications. In particular, bias stress was identified as the key instability under operation for numerous OTFT devices and interfaces. Despite a multitude of experimental observations, a comprehensive mechanism describing this behavior is still missing. Furthermore, controlled methods to overcome these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
0
43
1
Order By: Relevance
“…Dopants present in the channel, originating from either diffusion or bulk doping of the semiconductor, create a prominent issue: while the free‐charge generation of channel dopants increases mobility, they often dramatically increase the off‐current, too. Despite these challenges, doping has been used to tune and improve nearly every aspect of OFET operation including mobility, charge trapping, threshold voltage, stability, and injection …”
Section: Reducing Contact Resistance: Electrode Design and Beyondmentioning
confidence: 99%
“…Dopants present in the channel, originating from either diffusion or bulk doping of the semiconductor, create a prominent issue: while the free‐charge generation of channel dopants increases mobility, they often dramatically increase the off‐current, too. Despite these challenges, doping has been used to tune and improve nearly every aspect of OFET operation including mobility, charge trapping, threshold voltage, stability, and injection …”
Section: Reducing Contact Resistance: Electrode Design and Beyondmentioning
confidence: 99%
“…c) Time‐dependent I D characteristics for varied doping concentration with p‐ and n‐doped pentacene OFETs. Reproduced with permission . Copyright 2014, AIP Publishing LLC.…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
“…Hein et al reported the enhancement of the bias stress stability of a p‐type semiconductor (pentacene) OFET via the slight doping of the channel with 2,2′‐(perfluoronaphthalene‐2,6‐diylidene)dimalononitrile (F6‐TCNNQ, p‐dopant) or tetrakis(1,3,4,6,7,8‐hexahydro‐2H‐pyrimido[1,2‐a]pyrimidinato)ditungsten (W2(hpp)4, n‐dopant) . Under constant bias stress, the I D decay was found to be significantly reduced as the p‐dopant concentration increases (Figure b,c): the time constant parameter, τ, extracted from Equation , increases from 605 s (0 wt%) to 6.73 × 10 5 s (1 wt%, F6‐TCNNQ) with increases in the p‐dopant concentration.…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
“…For example, by doping separate charge transporting layers in organic solar cells and light emitting diodes charge selectivity can be ensured. Doping has also been utilized to deactivate traps in organic semiconductor devices and to reduce bias stress in organic transistors [10,11].…”
Section: Introductionmentioning
confidence: 99%